Psychological distress scale among caregivers in delivering care of patients with post-stroke rehabilitation: A validity and reliability testing study - Paramartadewi Paramartadewi; Khoiruddin Bashori; Nurul Hidayah (Journal of Holistic Nursing Science, 2023)
A stroke is a condition of blockage in the cardiovascular system. Patients who have passed the stroke phase are post-stroke rehabilitation patients who receive outpatient care. Caregivers help patients carry out daily activities during the rehabilitation process. Workload as a caregiver is a cause of psychological distress. The physical and emotional domains affect caregivers experiencing psychological distress, so caregivers become less psychologically healthy and less optimal in helping post-stroke rehabilitation patients. Researchers adapted the scale, namely Kessler's 10 Psychological Distress Scale (K-10), to see the level of psychological distress in caregivers of post-stroke rehabilitation patients—adaptation using Indonesian with the research participation of 43 people from Yogyakarta. Data were taken using accidental sampling on caregivers of post-stroke rehabilitation patients in Yogyakarta. Reliability testing was conducted using Cronbach's alpha, with the final result of p = 0.884, and construct validity testing using confirmatory factor analysis (CFA) with a measurement model. The results of this scale indicate that Cronbach's alpha is 0.884, and the CFA model is considered appropriate. Based on this, the results of this study suggest that the Psychological Distress Scale is reliable and valid so that it can be used for caregivers of post-stroke rehabilitation patients in Indonesia. In addition, this research scale can be used in health psychology, especially psychological distress. Keywords: Stroke; caregiver; nursing care; community care; rehabilitation care